Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/ijo.2017.225
|View full text |Cite
|
Sign up to set email alerts
|

A new animal diet based on human Western diet is a robust diet-induced obesity model: comparison to high-fat and cafeteria diets in term of metabolic and gut microbiota disruption

Abstract: These data suggest that diet, and not the obese state, was the major driving force behind gut microbiota changes. Moreover, the marked dysbiosis observed in CAF-fed rats might have resulted from the presence of several additives present in the CAF diet, or even a lack of essential vitamins and minerals. Based on our findings, we recommend the use of the prototypic WD (designed here) in DIO models. Conversely, CAF could be used to investigate the effects of excessive consumption of industrially produced and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
129
3
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(173 citation statements)
references
References 40 publications
11
129
3
12
Order By: Relevance
“…The HFHF diet group also showed a higher degree of steatosis than the HF diet group [168]. In a recent study, an HF sucrose pellet diet was administered to rats for 16 weeks, inducing significantly more pronounced steatosis, an increase in liver triglycerides and obesity compared to a pure HF diet treatment [169]. Surprisingly, the HF diet group in this study showed no increase in body weight or white fat deposits compared to the control diet group.…”
Section: Western Dietscontrasting
confidence: 52%
“…The HFHF diet group also showed a higher degree of steatosis than the HF diet group [168]. In a recent study, an HF sucrose pellet diet was administered to rats for 16 weeks, inducing significantly more pronounced steatosis, an increase in liver triglycerides and obesity compared to a pure HF diet treatment [169]. Surprisingly, the HF diet group in this study showed no increase in body weight or white fat deposits compared to the control diet group.…”
Section: Western Dietscontrasting
confidence: 52%
“…The aim of this study was to investigate whether weight loss improves the integrity of the DNA, which plays an important role in the etiology of various diseases that are associated with increased body mass (e.g., cancer, infertility, cognitive dysfunctions). Weight reduction was either achieved via restricted consumption of a Western diet (by 40%), which reflects the uptake of macronutrients in industrialized Western countries, [39] or by feeding an HCLP chow.…”
Section: Discussionmentioning
confidence: 99%
“…Diet-induced obesity has been modeled in mammals by supplementing diet with refined carbohydrates and fats (Levin et al 1989;Buettner et al 2007;Bortolin et al 2018). These studies have shown that diets high in fat and carbohydrates are capable of producing obesity in rat and mouse models with similar pathology to human obesity and produce associated comorbidities and metabolic syndromes.…”
Section: Discussionmentioning
confidence: 99%